IBIBIO MUSIC IN NIGERIAN CULTURE by Samuel Ekpe Akpabot, Michigan State University Press, 1975, pp. 102, $7.50. - Kubik, Gerhard (International Library of African Music, 1980)
pages: 130-131
Keywords: Ibibio (African people); African Music; Nigeria; Ibibio Music